Entstehung der subarktischen Grossstadt Workuta (Nordural) - Schaefer, Helmut (ERDKUNDE, 1957)
Vorkuta is the main centre of the northern Pechora coal basin and is situated at 67°30,N and 64°E. Like others of the new industrial centres of the U.S.S.R. it originated from a camp for political prisoners. Although its settlement and coal mining date back to 1929/30, a larger scale has only been reached since the outbreak of the second world war. After great efforts it was linked to the railway system in 1941. Since then Vorkuta coal has mainly served the Leningrad heavy industry. After the war this region, which was administratively included in the Komi-A.S.S.R., experienced a rise due to an improved supply of materials of all kinds. In connection with this, the death rate amongst the prisoners also declined. The annual production of coal is about 10 million tons. The present city is divided into Raiony which in their location follow the oval-shaped coal basin of about 20 km. in length and 15 km. in breadth. Most of the shafts, of which there are now about 20 in production, are situated at the margin of the coalfield and they are interconnected mainly by a circular railway line and motor way. The most distant places reached by branch lines are Chalmeryu, situated 120 km. south of the Arctic Sea coast, and the Ob river reached by a southern connecting line across the Urals. The old part of the town (Raion III), constructed during the war, is going downhill; the new part of the town (Raion I), however, is well supplied with pompous buildings and other installations. The technological possibilities of constructional work are handicapped by permafrost and an inimical climate, but are gradually being improved on the basis of experiments. The facilities for trade and life of the town are characterized by their up-to-date nature. Due to man's ability to civilize and the urge for survival amongst the forced labour stemming from all civilised nations, it has only taken a decade largely to gain the upper hand against the inimical forces of nature. Of these, extreme changes in air pressure are the most dangerous as far as health is concerned. Since life in the Samoyed tundra, with its sub-arctic continental climate, still remains difficult, the preservation of the labour force is Vorkuta's main problem. Mining operations are now greatly mechanized and obligatory labour of a great number of camp inmates is still insisted upon. For lack of frost-enduring crop species, agricultural development has so far been negligible. The keeping of domestic animals is however possible on a larger scale. The life of most of the non-prison population is poor and disorderly and in its contrast to the high living standards of the officials leads to social tension.